Origem e destino social de adultos cegos: trajetórias sociais e processos de escolarização - Soares, Antonio Francisco (2024)
This study aimed to analyze the social and educational trajectories of blind adults who, together with the physical condition caused by the disability, resulted in different social positions, based on the contributions of Bourdieu (1996, 2003, 2004), especially the concepts of social capital, as well as trajectories and strategies of social classification. In this sense, the following research problem was defined: In addition to the biological conditions caused by the disability, what are the distinctions, among the research participants, in the social destiny seen as a consequence, both in relation to their origins and the trajectories taken during the course of their lives? The empirical field selected was the city of Teresina (PI), not only because of the ease of access to research collaborators, but also to shift the focus to regions less investigated than those in the south-southeast axis, carried out by applying questionnaires for the social characterization of ten subjects, making up a diverse sample (sex, age, level of education, professional occupation), among which eight were willing to participate in comprehensive interviews, also based on this same author (BOURDIEU, 2001), which comprised the central core of the investigation. The most significant findings refer to the different social positions achieved in adulthood, as expressions of the social origin and the social and educational trajectories followed by these subjects